Efektivitas Pelaksanaan Putusan Perkara Kewarisan: Studi di Wilayah Hukum Pengadilan Agama Makassar Kelas IA - Soenandar, Dadang; Rahman, Sufirman; Zainuddin, Zainuddin (CV. Social Politic Genius (SIGn), 2023)
This study aims to determine and analyze the effectiveness of the implementation of inheritance case decisions in the Class IA Religious Court of Makassar and the factors that influence it. This type of research is empirical legal research with a qualitative descriptive in nature. This research was conducted at the Class IA Religious Court of Makassar. Data collection techniques used in this study were interviews, documentation, and literature study. The data analysis technique used is qualitative data analysis techniques. The results showed that the implementation of inheritance case decisions at the Class IA Religious Court of Makassar was still not effective. The factors that influence it include: delay in execution due to reasons of resistance; unclear lawsuit object, and high execution costs.